PROBLEMS AS METHODOF THE PROFESSIONAL ORIENTATION OF TEACHING MATHEMATICS AT TECHNICAL SPECIALTIES OF HIGHER EDUCTIONAL INSTITUTION - A. Seitmuratov; Z.A. Yergalauova; L.S. Kainbayeva; G.K. Yeshmurat (Academic Journal of Physical and Chemical Sciences, 2019)
The article deals with the problem of the professional orientation of teaching mathematics at technical specialties of a higher educational institution andthe analysis of the resourcesconcerning the solution of problems with professional content, their selection and ranking has been made as well. The article focuses on the didactic conditions that professionally oriented problems must coincide with in training future engineers for their successful application, the classification of problems with professional content, as well as ways to solve such problems. The main requirements for problems with professional content are shown and the problem on the theme "Application of a certain integral to pressure calculation" is considered.